Study Of Role Of Digitization In Sustainable Business In Auto Industry In India Using Thematic Content Analysis, Spearman Analysis And Review Of Literature. - et. al., Prakash D. Wagh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Progress in digital technologies and Cyber physical technologies in last one decade has created immense opportunities for business firms and companies to adopt sustainable practices in their end to end business cycle. This is helping business to conserve the various resources like energy, material ,manual efforts, water and contributing to lower cost of goods sold ,ultimately making the balance sheet and profit and loss account green and healthy. The consumer and NGO pressures , Government rules and regulations and depleting resources is also acting as a trigger for businesses to adopt sustainability. Digitization is helping companies in achieving the sustainability aspect in their operations ,supply chain and other parts of the business. This paper is based on the interaction and interviews with 40 business leaders from Automobile industry in India during the last 2 years and literature study of digitization and sustainability goals and other related research articles. The interview output was analyzed using thematic sematic analysis (TMC) and collaborated with finding from review of literate. The study concluded that there is enough positive and significant relationship between Digitization and sustainability ( Sustainable business) in Auto industry in India.